2007
DOI: 10.1590/s0100-84042007000400010
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the vegetation on a highland granitic rock outcrop in Southeast Brazil

Abstract: -(Structural analysis of the vegetation on a highland granitic rock outcrop in Southeast Brazil). Granitic rock outcrops of the Brazilian southeast are either coastal or inland. The latter can often have high altitudes, such as in the summits of "Serra do Mar" and "Serra da Mantiqueira", where they are known as "Campos de Altitude". The landscape on these high altitude plateaux is often a mosaic of shrubs and treelets within a bunchgrass matrix, with sparse pteridophytes and other herbs, interspersed with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
(19 reference statements)
2
17
0
9
Order By: Relevance
“…Em Monte Verde, os Afloramentos Rochosos estão envoltos por matriz florestal e observa-se a formação de um escrube pouco extenso nas suas bordas. Asteraceae, Cyperaceae, Melastomataceae, Orchidaceae, Poaceae, Polygalaceae e Rubiaceae estão entre as famílias mais ricas nos afloramentos rochosos imersos em formações florestais no Sudeste brasileiro (Meirelles et al 1999;Safford & Martinelli 2000;Caiafa & Silva 2007;Ribeiro et al 2007). Cyperaceae geralmente não é citada como uma das famílias mais ricas em afloramentos rochosos no Sudeste, entretanto espécies dessa família são citadas como as principais espécies formadoras das ilhas de vegetação sobre afloramentos graníticos e sobre nifelina-sienito no Sudeste do Brasil (Caiafa & Silva 2007;Medina et al 2006 (Burkart 1979;Azevedo 1981;Landrum 1984;Mentz & Oliveira 2004).…”
Section: Distribuição Geográficaunclassified
“…Em Monte Verde, os Afloramentos Rochosos estão envoltos por matriz florestal e observa-se a formação de um escrube pouco extenso nas suas bordas. Asteraceae, Cyperaceae, Melastomataceae, Orchidaceae, Poaceae, Polygalaceae e Rubiaceae estão entre as famílias mais ricas nos afloramentos rochosos imersos em formações florestais no Sudeste brasileiro (Meirelles et al 1999;Safford & Martinelli 2000;Caiafa & Silva 2007;Ribeiro et al 2007). Cyperaceae geralmente não é citada como uma das famílias mais ricas em afloramentos rochosos no Sudeste, entretanto espécies dessa família são citadas como as principais espécies formadoras das ilhas de vegetação sobre afloramentos graníticos e sobre nifelina-sienito no Sudeste do Brasil (Caiafa & Silva 2007;Medina et al 2006 (Burkart 1979;Azevedo 1981;Landrum 1984;Mentz & Oliveira 2004).…”
Section: Distribuição Geográficaunclassified
“…Therefore, further studies and surveys are required in order to obtain a more widely applicable ecological knowledge. However, we conducted a brief analysis relating to upper montane grasslands of the present study with other vegetation studies about altitude rocky outcrops in Serra da Mantiqueira (Southeastern Brazil) (Caiafa & Silva 2007, Ribeiro et al 2007, Tinti et al 2015 as well as two sites of Serra do Mar (Araras & Madalena) in the State of Rio de Janeiro (Meirelles et al 1999). We learned that neither of the species found in the upper montane grasslands within Serra do Mar in Paraná was found in these two areas in Rio de Janeiro.…”
Section: Structure Of Upper Montane Grasslands In the State Of Paranámentioning
confidence: 84%
“…Perhaps because such species might be more adapted to grasslands than rocky outcrops. Based on studies carried out at Serra da Mantiqueira only two species were found (Caiafa & Silva 2007) to approximately two dozen species (Tinti et al 2015) in common with the ones found within the subranges studied in Paraná, which in addition to the distances between them, may be related to the surrounding phytogeographic aspects. The floristic study reported by Tinti et al (2015) (Serra do Brigadeiro -Mantiqueira, in the State of Minas Gerais) is in alignment with the grasslands of our study, for instance, the following taxa: Achyrocline satureoides, Stevia clausseni, Gaultheria serrata, "Croton mullerianus"(Croton splendidus), Hesperozygis nitida, Lycopodium clavatum, Doryopteris crenulans and Galium hypocarpium.…”
Section: Structure Of Upper Montane Grasslands In the State Of Paranámentioning
confidence: 88%
See 2 more Smart Citations